Morphological and physiological-biochemical variability of spore-forming bacteria isolated from the agrocoenosis of winter wheat - Honchar, A.; Tonkha, O.; Patyka, N.; Lykholat, Y.; Patyka, T. (Regulatory Mechanisms in Biosystems, 2021)
From an agrocoenosis of winter wheat (Triticum aestivum L.; phylloplane and rhizosphere of the root system; typical chernozem, soil column measuring up to 40 cm), using the classical microbiological methods, we had isolated soil bacteria and characterized them according to the morphological features as representatives of Gram-positive and spore-forming bacteria of Bacillus sp. genus. In the earing-swelling phase of grain, the screening studies found non-pigmented forms of colonies of bacterial isolates, 19 of which were classified to colonial-morphological diversity of R-type with the diameter of 7 to 13 mm. The analysis of physiological condition of cells of populations of soil isolates revealed technologic specificity according to parameters of spore formation in different conditions and incubation time (up to 48–72 h). We observed 90.0% of free spores in axenic cultures as early as after 72 h of cultivation and no more than 10.0% of prospores in the studied monoisolates with stable morphologic traits. Isolates Н10 and Н45 demonstrated the ability to grow in higher cultivation temperatures (+37…+40 °С). According to environmental рН, isolates were able to grow in рН ranging 4.5–8.0. Differential diagnostic testing revealed that as the source of carbon, with formation of acid, soil isolates used arabinose, xylose, mannitol, glucose, galactose, fructose, maltose, sorbitol, glycerin, dextrin, starch, rhamnose and dulcite (with development of alkaline). There was observed active use of mineral forms of nitrogen: ammonium salt and nitrates, aminoacids and proteins. The isolates hydrolyzed casein, gelatin, starch, and litmus was being reduced in the young during growth in milk with litmus. They also exerted catalase activity and were oxidase-positive. Biochemical testing using API test system determined that the studied isolated bacteria differed by a range of fermentation carbohydrates, reduction of nitrates. In the conditions of submerged fermentation, isolates Н38 and Н40 grew in heightened temperature ranges of cultivation (40 °С) for 48 h (according to fact of spore development). Therefore, according to the key morphologic and biochemical traits, strains Н3, Н10, Н13, Н36, Н38, Н40, Н43, Н45 were similar to such of reference strain B. subtilis 8A, and were identified to Bacillus sp., species B. subtilis.